2020
DOI: 10.1016/j.ecoenv.2020.111116
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of ecological hazards and environmental fate of disinfectant quaternary ammonium compounds

Abstract: Disinfectant quaternary ammonium compounds (Quats) have diverse uses in a variety of consumer and commercial products, particularly cleaning products. With the emergence of the COVID-19 pandemic, they have become a primary tool to inactivate the SARS-CoV-2 virus on surfaces. Disinfectant Quats have very low vapor pressure, and following the use phase of the products in which they are found, disposal is typically “down-the-drain” to wastewater treatment systems. Consequently, the potential for the greatest envi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(64 citation statements)
references
References 48 publications
0
56
0
1
Order By: Relevance
“…From a macroperspective, every country must implement a series of measures immediately. In addition, different countries should take different measures nationally or subnationally based on their specific contexts, management systems, and characteristics [2].…”
Section: Introductionmentioning
confidence: 99%
“…From a macroperspective, every country must implement a series of measures immediately. In addition, different countries should take different measures nationally or subnationally based on their specific contexts, management systems, and characteristics [2].…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of neural tube defects (NTDs) on gestation days (GD) 10 or 11 increased in offspring from dams in the treated rooms versus those in untreated rooms. 3 It is interesting to note that the authors point out that: "Despite the NTDs observed in GD 10 embryos, we did not see exencephaly in late gestation fetuses. This was unexpected as NTDs are not lethal to the developing fetus.…”
Section: Non-guideline Studiesmentioning
confidence: 62%
“…The effectiveness of these biocides in impairing the photosynthesis is determined by their chemical composition, rich in quaternary ammonium compounds (i.e., didecyl-dimethyl ammonium chloride, DDAC, and BAC, respectively) as active components [16]. They are well-known xenobiotics with a notable algicidal action [35][36][37][38], produced by their remarkable capacity to disrupt cell membranes [39], which causes the release of intracellular metabolites and the degradation of proteins and nucleic acids, until cell lysis [40]. In addition, OIT showed a marked efficacy against algae, as reported in toxicity tests using the algae Scenedesmus vacuolatus and Selenastrum capricornutum [26,41], even if following a different mechanism of action (i.e., the blocking of the enzymatic pathway of cysteines in proteins active sites, respiration, ATP synthesis and metabolism) [22,26].…”
Section: Discussionmentioning
confidence: 99%